Pemberdayaan Kesehatan Reproduksi Remaja Anggota Bina Keluarga Remaja (BKR) melalui Participatory Rural Appraisal (PRA) di Desa Potorono, Kabupaten Bantul, Daerah Istimewa Yogyakarta - Ratu Matahari; Khoiriyah Isni; Fitriana Putri Utami (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2021)
The lack of open communication between parents and children triggers adolescents to engage in deviant behavior, including premarital sex. This activity aims to improve the knowledge and communication skills of BKR members regarding adolescent reproductive health as an effort to reduce the incidence of unwanted pregnancy and early marriage in Padukuhan Mertosanan Kulon, Potorono Village. The interventions provided were in the form of counseling and roleplay as well as discussion of case studies related to adolescent reproductive health. Based on the results of the intervention, knowledge about reproductive health increased, participants were skilled in solving problems in case studies and were able to practice health communication to adolescents. It is very important to carry out regular adolescent reproductive health education activities for BKR members.